2017
DOI: 10.3390/f8040130
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Drives SOC Accumulation, Its Temperature Stability and Turnover in Forests, Northeastern China

Abstract: Global urbanization is a vital process shaping terrestrial ecosystems but its effects on forest soil carbon (C) dynamics are still not well defined. To clarify the effects of urbanization on soil organic carbon (SOC) variation, 306 soil samples were collected and analyzed under two urban-rural gradients, defined according to human disturbance time and ring road development in Changchun, northeast China. Forest SOC showed a linear increase with increasing human disturbance time from year 1900 to 2014 (13.4 g C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Harbin (Lv et al, 2016), and the same findings were reported in Changchun, China (Zhai et al, 2017). The aggregation and shape complexity of patches decreased (in terms of LSI increased)…”
Section: Implications For the Urban Forest Evaluation And Uncertaintysupporting
confidence: 76%
See 2 more Smart Citations
“…Harbin (Lv et al, 2016), and the same findings were reported in Changchun, China (Zhai et al, 2017). The aggregation and shape complexity of patches decreased (in terms of LSI increased)…”
Section: Implications For the Urban Forest Evaluation And Uncertaintysupporting
confidence: 76%
“…Specific designs, such as demolition of illegal structures for tree planting, replanting trees in vacant lots that surround by buildings (Bajsanski et al, 2016;Zhao, 2017;Zhao et al, 2017), and implementation of vertical greening on roofs, walls, and bridges, may increase the connectivity of urban forests and have a positive influence on the fragmented landscape (Gao & Yu, 2014). Previous studies have highlighted that urban greening practices should consider the importance of biodiversity conservation (Xiao et al, 2016a), removal of pollutants (Escobedo & Nowak, 2009;Mu et al, 2004), urban microclimate regulations (Wang et al, 2018), urban heat island mitigation (Zhang et al, 2017a), and urban soil improvement (Cui & Mu, 2016;Wang et al, 2017;Zhou et al, 2017). Our findings strongly suggest that urban forest carbon sequestration in both aboveground biomass and belowground soil carbon should be considered for coimprovement of multiple ecological services.…”
Section: Landscape Metrics Responsible For Carbon Variations and Highmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology enabled us to compare the difference of facial expressions between forests at urban and rural areas. The urban-rural comparison can reflect the environmental and anthropogenic changes caused by urbanization [52,53]. However, in studies on emotional perception in response to nature experience, the urban environment was usually taken as the reference (or the control) to quantify participants' performance in a forest [7,9,19].…”
Section: The Limitations Of the Current Studymentioning
confidence: 99%
“…Structural equation modeling (SEM) is a powerful, multivariate technique found increasingly in scientific investigations to test and evaluate multivariate causal relationships 25 , and powerful in soil ecology from patterns to causalunderstanding 26 . Pearson correlation and stepwise regression are common-used methods for finding complex associations and possible casual relations 2730 . Canonical ordinations are invaluable tools for modeling communities through environmental predictors, and variation partitioning can then be used to test and determine the likelihood of these sets of predictors in explaining patterns in community structure 31 , is also powerful in identifying co-occurring species on translocation success in Iris atrofusca 32 .…”
Section: Introductionmentioning
confidence: 99%